Conductive cobalt doped niobium nitride porous spheres as an efficient polysulfide convertor for advanced lithium-sulfur batteries. Issue 13 (19th March 2020) - Ge, Weini; Wang, Lu; Li, Chuanchuan; Wang, Chunsheng; Wang, Debao; Qian, Yitai; Xu, Liqiang
Abstract : Porous Co-NbN spheres with excellent conductivity are used as sulfur hosts for lithium-sulfur batteries, which deliver excellent long-term cycle stability and performance with a high sulfur loading and lean electrolyte. Abstract : The lithium-sulfur battery has been considered as one of the potential candidates for energy storage devices owing to its high theoretical specific capacity and superior energy density. However, its practical application still faces challenges such as low sulfur utilization, the serious shuttle effect of polysulfides and large volume expansion, especially upon high areal sulfur loading. Herein, conductive cobalt doped niobium nitride (Co-NbN) porous spheres as a novel kind of sulfur host material have been fabricated via a facile solvothermal and subsequent calcination process under ammonia. The obtained Co-NbN/rGO/S cathode delivers an excellent rate performance of up to ∼600 mA h g −1 at 1C with a relatively high areal loading of 3.3 mgs cm −2 and an excellent long–term cycle stability of 404.5 mA h g −1 after 800 cycles at 1C (the decay rate is only 0.07% per cycle) with a sulfur loading of 72%. It is worth noting that the cathode exhibited a superior areal capacity of 3.92 mA h cm −2 at a high sulfur loading of 5.6 mgs cm −2 with a lean electrolyte (E/S = 8 μL mgsulfur −1 ). It is considered that the conductive and polar niobium nitride could effectively improve sulfur utilization and polysulfide anchoring of the sulfur cathode, and its unique porous structure could effectively accommodate the distribution of the sulfur species and inhibit volume expansion of the cathode. In addition, the synergistic effect between cobalt and NbN further facilitated the conversion of sulfur species, suppressing the shuttle effect and accelerating electrochemical kinetics. The porous Co-NbN based host material has great potential for practical application in lithium-sulfur batteries.